Oocytes Population and Development Competence of Bali Cattle Embryo In Vitro with Different Ovarian Reproductive Statuses - H. Hasbi; H. Sonjaya; S. Gustina (Faculty of Animal Science, Bogor Agricultural University, 2022)
The present study aims to determine the potential of Bali cattle ovaries as sources of oocytes for in vitro embryo production based on different ovarian reproductive statuses. The ovaries were grouped into 4 categories: ovaries with no corpus luteum and dominant follicles (CL-DF-), those with corpus luteum and no dominant follicles (CL+DF-), those without corpus luteum but with dominant follicles (CL-DF+), and those with corpus luteum and dominant follicle (CL+DF+). The oocytes were collected via the slicing technique and grouped into 4 grades (a, b, c, and d). The oocyte’s maturation was performed using tissue culture medium 199 basic media. A drop sample (10–15 oocytes/drop) covered with mineral oil was then placed in a 5% CO2 incubator at a temperature of 38.5 ℃ for 24 h. Then, the samples were fertilized in 80 μL of fertilization medium with a final spermatozoa concentration of 1.5×106 spermatozoa/mL. After 5–6 h of in vitro fertilization, the oocytes were washed four times using the Charles Rosenkrans 1aa (CR1aa) medium. Then, the samples were cultured using the CR1aa as a base medium. The results showed no significant difference (p>0.05) for the 4 groups based on the oocyte population collected from one pair ovary as well as the number of oocytes that were suitable for maturation. However, group CL-DF+ showed a significant difference (p<0.05) in the rate of nuclear maturation (80.00±12.84), fertilization rate (80.00±4.72), and the ability of embryo development (60.19±22.45) when compared to group CL-DF-, CL+DF-, and CL+DF+. This study determines that the oocyte population of Bali cattle ovary pairs and oocytes quantity that are fit for maturation is not influenced by the reproductive status of the ovaries. However, the level of nuclear maturation, fertilization, and the ability of embryo development is higher in the ovaries without corpus luteum but with dominant follicles.